Does foliar silicon application enhance the biomass yield of millet silage, and does it provide significant economic gains? (Research, Society and Development, 2021)
Millet is a grass that has been highlighted for silage production, especially for being a productive tropical plant, and undemanding concerning soil fertility. Silicon (Si) is an alternative low-cost solution to increase biomass production, and it has been noticed to be beneficial to plants, especially when there are stress conditions. So, we analyzed the effects of foliar silicon application to gas exchanges, dry biomass production, and economic efficiency. We used a completely randomized experimental design consisting of foliar application of the following five doses of Si: 0; 0.84; 1.68; 2.52; and 3.36 g L-1 of Si as potassium and sodium silicate, with five replications. We measured the plant height, leaf area, Si contents and accumulation in the plants, gas exchanges (stomatal conductance, transpiration, and photosynthesis net), dry matter production, Si uptake and transport efficiency by plants and its economic efficiency. The Si content enhanced and accumulated in all parts of millet plants, reaching values between 2.5 and 3.3 g L-1. There were linear increases of approximately 9 and 27% in height and leaf area of millet plants to 3.36 g L-1 of Si. Stomatal conductance and transpiration reached maximum values representing an increase of 44.60 and 101.30%, respectively. The concentration of 3.36 g L-1 of Si increased photosynthesis by 76% and shoot dry matter production by 15%, when compared to the control. Si application is economically viable. The operational costs of application are suppressed, reaching to about US $ 45.32 ha-1 with the application of 2.52 g L-1 of Si.